2014
DOI: 10.1007/s11064-014-1498-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of (E)-2-(1-Hydroxyl-4-Oxocyclohexyl) Ethyl Caffeine Against Hydrogen Peroxide-Induced Injury in PC12 Cells

Abstract: (E)-2-(1-hydroxyl-4-oxocyclohexyl) ethyl caffeine (HOEC), a naturally caffeic ester isolated from Incarvillea mairei, has been reported to possess anti-inflammatory activity by targeting 5-lipoxygenase. However, its other potential activities have yet to be explored. In this study, we measured antioxidant activity of HOEC using the DPPH free radical-scavenging assay. Then, we exposed rat pheochromocytoma (PC12) cells to hydrogen peroxide (H2O2)-induced damage and investigated the antioxidant activity of HOEC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…However, the focus of our work is to investigate the effects of propofol against oxidative stressrelated neurological disorders and the underling mechanisms, which is very different from Hsu'work, and this is also the major contribution of our work. In our current study, the rat differentiated PC12 cell was subjected to H 2 O 2 exposure to mimic a neuronal in vitro model of oxidative injury, previous researches (Hwang and Yen 2008;Li et al 2013;Wei et al 2014;Chen et al 2014) have demonstrated that the concentration of H 2 O 2 selected (250 lM) in our study is within the concentration range of H 2 O 2 typically identified in neurological disorders. We found that propofol-induced attenuation of NOX2 expression and NOX activity is involved in its cytoprotective effects against H 2 O 2 -induced oxidative injury in PC12 cells.…”
Section: Discussionmentioning
confidence: 66%
“…However, the focus of our work is to investigate the effects of propofol against oxidative stressrelated neurological disorders and the underling mechanisms, which is very different from Hsu'work, and this is also the major contribution of our work. In our current study, the rat differentiated PC12 cell was subjected to H 2 O 2 exposure to mimic a neuronal in vitro model of oxidative injury, previous researches (Hwang and Yen 2008;Li et al 2013;Wei et al 2014;Chen et al 2014) have demonstrated that the concentration of H 2 O 2 selected (250 lM) in our study is within the concentration range of H 2 O 2 typically identified in neurological disorders. We found that propofol-induced attenuation of NOX2 expression and NOX activity is involved in its cytoprotective effects against H 2 O 2 -induced oxidative injury in PC12 cells.…”
Section: Discussionmentioning
confidence: 66%
“…Previous study corroborated that miRNAs play critical roles in various ailments which are linked to oxidative damage [30]. MiR-26a is a crucial miRNA, which has been reported in multitudinous cancers [31,32] The mitochondria-dependent apoptotic pathway has been disclosed to join in H 2 O 2 -triggered cytotoxicity in PC-12 cells [34]. It has been testified that PI3K/AKT and MEK/ERK pathways are the dominating pro-survival pathways within the cells [35].…”
Section: Discussionmentioning
confidence: 70%
“…Previous papers reported that H 2 O 2 had cytotoxic effects in various in vitro model by a mechanism involving pro-apoptotic factors (Bax, caspases, PARP) activation and intracellular signaling pathway [ 45 51 ]. Especially, MAPK signaling pathway has been suggested as an important mechanism in oxidative stress-mediated neurodegenerative diseases [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%